An original amino acid formula favours in vitro corneal epithelial wound healing by promoting Fn1, ITGB1, and PGC-1α expression. (June 2022) - Tedesco, Laura; Rossi, Fabio; Ruocco, Chiara; Ragni, Maurizio; Carruba, Michele O.; Valerio, Alessandra; Nisoli, Enzo
Abstract: Corneal disorders are frequent, involving most diabetic patients; among its manifestations, they include delayed wound healing. Since maintenance of mitochondrial homeostasis is fundamental for the cell, stimulation of mitochondrial biogenesis represents a unique therapeutic tool for preventing and treating disorders with a deficit in energy metabolism. We have recently demonstrated that a branched-chain amino acid (BCAA)-enriched mixture (BCAAem) supported mitochondrial biogenesis in cardiac and skeletal muscle, reduced liver damage caused by alcohol, and prevented the doxorubicin-dependent mitochondrial damage in cardiomyocytes. The present study aimed to investigate a new amino acid mixture, named six amino acids (6AA), to promote corneal epithelial wound healing by regulating mitochondrial biogenesis. A murine epithelium cell line (TKE2) exposed to this mixture showed increased mitochondrial biogenesis markers, fibronectin 1 (Fn1) and integrin beta 1 (ITGB1) involved in extracellular matrix synthesis and cell migration. Most importantly, the 6AA mixture completely restored the wound in scratch assays, confirming the potential of this new formula in eye disorders like keratopathy. Moreover, our results demonstrate for the first time that peroxisome proliferator-receptor γ coactivator 1 α (PGC-1α) is expressed in TKE2 cells, which controls mitochondrial function and corneal repair process. These results could be relevant for the treatment mainly focused on corneal re-epithelialisation. Highlights: TKE2 cell represents an adequate experimental model to study corneal repair. The 6AA mixture promotes the expression of Fn1, ITGB1 and mitochondrial markers. The 6AA mixture promotes the corneal repair process. The master regulator of mitochondrial biogenesis PGC1-α is expressed in TKE2 cells.